Karakteristik dan efek samping pemberian vaksinasi Covid-19 terhadap tenaga kesehatan - Rachmat Faisal Syamsu; Innayaturrahmatiah Innayaturrahmatiah; Eny Arlini Wello; Indah Lestari Daeng Kanang; Imran Safei (Holistik Jurnal Kesehatan, 2024)
Background: On January 13 2021, Indonesia authorized the Covid-19 vaccine for emergency use and started a national vaccination program. The Ministry of Health, with support from UNICEF and WHO, carried out an online survey to understand the public's views, perceptions and concerns regarding Covid-19 vaccination. The results obtained showed that 8% of them refused, the remaining 27% expressed doubts about this vaccination, so there is a need for outreach to the public regarding the importance of vaccination, as well as its safety, the type of vaccine used and knowing the side effects felt by each individual who has had it. get vaccinated. Purpose: To determine the characteristics and side effects of administering Covid-19 vaccination to health workers Method: This research is observational analytic with a cross sectional method using a questionna ire filled out by health workers at RSUP Dr. Johannes Leimena Ambon who has taken part in stages 1 and 2 of vaccination with the brand Sinovac (coronavac), numbering 173 people. Results: As many as 80% of respondents did not experience post-vaccination side effects, 20% experienced at least one local symptom and systemic symptoms which were mostly experienced by female health workers in the 26-35 year age group. Conclusion: Ages 26-35 years, female, and nursing staff constitute the majority of respondents who did not experience side effects after stages 1 and 2 of Covid-19 vaccination.   Keywords: Adults; Covid-19; Hospital; Vaccination.   Pendahuluan: Pada 13 Januari 2021, Indonesia telah mengesahkan vaksin Covid-19 untuk penggunaan darurat dan memulai program vaksinasi nasional. Kementerian kesehatan dengan dukungan dari UNICEF dan WHO, melaksanakan survei daring untuk memahami pandangan, persepsi, dan kekhawatiran publik terkait vaksinasi Covid-19. Hasil yang didapat menunjukan bahwa 8% di antaranya menolak, 27% sisanya menyatakan ragu dengan vaksinasi ini, sehingga perlu adanya sosialisasi ke masyarakat mengenai penting nya melakukan vaksinasi, serta keamanannya, jenis vaksin yang digunakan dan mengetahui efek samping yang dirasakan pada setiap individu yang telah melakukan vaksinasi. Tujuan: Untuk mengetahui karakteristik dan efek samping pemberian vaksinasi Covid-19 terhadap tenaga kesehatan Metode: Penelitian ini bersifat analitik observasional dengan metode cross sectional menggunakan kuesioner yang diisi oleh tenaga kesehatan di RSUP Dr. Johannes Leimena Ambon yang telah mengikuti vaksinasi tahap 1 dan 2 dengan merek sinovac (coronavac) yaitu berjumlah 173 orang. Hasil: Sebanyak 80% responden tidak mengalami efek samping pasca vaksinasi, 20% mengalami setidaknya satu gejala lokal dan gejala sistemik yang banyak dialami oleh tenaga kesehatan perempuan dengan kelompok usia 26-35 tahun. Simpulan: Usia 26-35 tahun, jenis kelamin perempuan, dan tenaga perawat merupakan mayoritas responden yang tidak mengalami efek samping pasca vaksinasi Covid-19 tahap 1 dan 2.   Kata Kunci: Covid-19; Orang Dewasa; Rumah Sakit; Vaksinasi.